SASTRA DALAM TRADISI PENDIDIKAN ISLAM - Sunhaji Sunhaji (IBDA` : Jurnal Kajian Islam dan Budaya, 2015)
This article stands on the idea that the spread and progress of Islam along the Indonesian Archipelago is influenced by literary works. They have become an important learning in Islamic boarding schools (Pesantren), which is intended to drive students (santri) not only to memorize al-Qurâ€™an and hadits, but also implement them in their real life. This condition can be seen in in the story telling method, which can develop certain characters through appreciating every aspect of life and learning to reproduce the good sides and avoid the bad ones. In such a condition, literary works can be used as a media, a method, even a strategy of learning.Â Tulisan ini diasumsikan dari pola pikir bahwa Islam Nusantaradipengaruhi oleh karya sastra. Karya sastra menjadi pembelajaran penting di pondok pesantren. Kondisi ini dapat dilihat dalam metode pembelajaran kisah yang dapat membentuk karakter melalui penghayataan setiap sisikehidupan sehingga orang bisa belajar untuk meniru tokoh tersebut apabila baik, juga dapat untuk tidak mengulangi kejadian-kejadian buruk yang ada dalam kisah. Dalam hal ini, karya sastra dapat menjadi media pembelajaran, metode, bahkan strategi pembelajaran.